The Permai Community in Penang, Malaysia Through Digital Literacy to Prevent Illegal Online Loans : Pengabdian - Nurhayani Saragih; Leila Mona Ganiem (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The misuse of illegal online loans (known as pinjol) among Indonesian diaspora communities in Malaysia highlights the urgent need to improve digital and financial literacy. This community service program, conducted by Universitas Mercu Buana in collaboration with PERMAI in Penang, aimed to strengthen community resilience through participatory, community-based education. Employing a Participatory Action Research (PAR) approach, the program involved a needs assessment, interactive training sessions, real-case simulations, group discussions, and digital awareness campaigns. Educational materials focused on identifying illegal lending practices, protecting personal digital data, making informed financial decisions, and using social media for financial advocacy. Evaluation results indicated increased knowledge, greater awareness of digital risks, and more cautious financial behavior among participants. Quantitative data showed high levels of satisfaction, while qualitative feedback confirmed behavioral change and active community engagement. Additionally, the program contributed to achieving institutional Key Performance Indicators (KPIs) and enhanced PERMAI’s role as a digital literacy hub for the Indonesian diaspora in Malaysia.